2022
DOI: 10.1002/ana.26464
|View full text |Cite
|
Sign up to set email alerts
|

Association between Human Blood Metabolome and the Risk of Alzheimer's Disease

Abstract: ObjectiveAlzheimer's disease (AD) is the most common degenerative neurological disorder with limited therapeutic options. Therefore, it is particularly important to explore the potential biomarkers implicated in the occurrence and progression of AD prior to clinical testing.MethodsWe selected 119 unique blood metabolites from 3 metabolome genome‐wide association studies (GWASs) with 147,827 European participants. Summary data about AD were obtained from a GWAS meta‐analysis with 63,926 European individuals fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Our finding is in line with another previous study (Sun et al, 2022) that demonstrated a negative association between circulating levels of Gln and the risk of AD. In contrast, another observational study (Cui et al, 2020) showed the opposite correlation to our results.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our finding is in line with another previous study (Sun et al, 2022) that demonstrated a negative association between circulating levels of Gln and the risk of AD. In contrast, another observational study (Cui et al, 2020) showed the opposite correlation to our results.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, one study using MR analysis demonstrated a negative association between circulating levels of glutamine and the risk of Alzheimer's disease (Sun et al, 2022). However, Mei Cui et al (Cui et al, 2020) found an opposite correlation to the MR study described above.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This assertion was substantiated in a subsequent study investigating the correlation between sex hormones and AD risk. However, caution is advised in clinical practice, as a Phe-MR analysis by Sun et al suggested potential detrimental effects of epiandrosterone sulfate on respiratory and digestive diseases (Sun et al, 2022). Thus, while epiandrosterone sulfate may hold promise as a therapeutic target for AD, careful consideration of potential adverse side effects is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Mendelian randomization (MR) is an emerging approach that uses genetic variation as an instrumental variable (IV) for the exposure of interest to estimate the causal relationship between exposure and disease without confounding or reverse causality biases 10 . To date, MR studies of blood metabolites in various diseases such as epilepsy, 11 Alzheimer's disease 12 and lacunar stroke 13 have been conducted by related scholars, but MR studies of blood metabolites in COVID‐19 have not been performed. Therefore, this study used MR analysis to explore the causal relationship between blood metabolites and severe COVID‐19, providing clues to unravel the pathogenesis of COVID‐19 and thus offering new ideas for the prediction and treatment of severe COVID‐19.…”
Section: Introductionmentioning
confidence: 99%